Direct Torque Control of Four Switch Three Phase Inverter fed Induction Motor Sensorless Speed Drive - Mohamed K Metwally (Institute of Advanced Engineering and Science, 2014)
This paper presents sensorless speed control of induction motor (IM) using four switch three phase inverter (FSTPI) with direct torque and flux control (DTFC). The proposed sensorless DTFC system consists of an adaptive observer of rotor flux to accurately estimate stator resistance and speed simultaneously, without affecting drive performances. The switching technique for DTFC of IM using FSTPI in low power application is based on the principle of similarity between FSTPI and SSTPI (six switch three phase inverter), where the αβ plan is divided into 6 sectors and the formation of the voltage space vector is done in the same way as for SSTPI by using effective (mean) vectors. This approach allows using the well-known established switching table of SSTPI for FSTPI. The simulation results indicates that the sensorless speed control of FSTPI fed IM with DTFC and adaptive observer provides accurate estimate, good trajectory tracking with different dynamics performance. The experimental results verify the effectiveness of the proposed method at different operating points.DOI: http://dx.doi.org/10.11591/ijpeds.v5i2.5645